Respostas

2013-05-28T14:44:53-03:00

x² - 14x + 48 = 0

 

a = 1

b = -14

c = 48

 

x = -b ± √¯Δ

 

Δ = b² - 4ac

Δ = (-14)² - 4 . 1 . 48

Δ = 196 - 192

Δ = 4

 

x = - (-14) ± 4 / 2 . 1

x = 14 ± 2 / 2

 

x ' = 14 + 2 / 2

x ' = 16 / 2

x ' = 8

 

x ' ' = 14 - 2 / 2

x ' ' = 12 / 2

x ' ' = 6

  • Usuário do Brainly
2013-05-28T16:48:49-03:00

Temos que:

 

\text{x}^2-14\text{x}+48=0

 

\text{x}=\dfrac{-(-14)\pm\sqrt{(-14)^2-4\cdot1\cdot48}}{2\cdot1}=\dfrac{14\pm2}{2}

 

Logo, as raízes são:

 

\text{x}'=\dfrac{14+2}{2}=8

 

\text{x}"=\dfrac{14-2}{2}=6